Chemo‐ and Stereoselective Cross Rauhut–Currier‐Type Reaction of Tri‐substituted Alkenes Containing Trifluoromethyl Groups. Issue 8 (10th January 2018) - He, Xiang‐Hong; Yang, Lei; Ji, Yan‐Ling; Zhao, Qian; Yang, Ming‐Cheng; Huang, Wei; Peng, Cheng; Han, Bo
Abstract: A chemoselective cross Rauhut–Currier‐type reaction has been developed involving a tri‐substituted alkene (trifluoromethyl‐containing acrylonitrile derivative) with a di‐ or tri‐substituted alkene to yield tetra‐substituted double bonds in RC‐type products. This approach can support the synthesis of trifluoromethylated tetra‐substituted olefins and synthetically important, structurally complex 3‐allylic‐type oxindole skeletons. The asymmetric version of this RC‐type reaction can be realized by combining a Brønsted acid and Lewis base for bifunctional H‐bonding‐tertiary amine catalysis. Subsequent transformation of multi‐functionalized RC‐type product leads to pharmacologically interesting cyclohexane‐based spiro‐pyrazolones bearing six contiguous chiral centers and two highly congested, vicinal quaternary carbon centers. Abstract : A chemoselective cross‐Rauhut–Currier ‐type reaction has been developed involving a tri‐substituted alkene (CF3 ‐containing acrylonitrile derivative) is described. This approach can support the synthesis of trifluoromethylated tetra‐substituted olefins and 3‐allylic‐type oxindole skeletons. The transformation of multi‐functionalized chiral RC‐type product leads to pharmacologically interesting cyclohexane‐based spiro‐pyrazolones bearing six contiguous chiral centers.